UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOLIK DAUN KELOR (Moringa oleifera Lamk.), DAUN TEH HIJAU (Camellia sinensis L.), DAUN BINAHONG (Anredera cordifolia (Tenore) Steen.), DAN MENIRAN HIJAU (Phyllanthus niruri L.) TERHADAP Pseudomonas aeruginosa ATCC 27853 - Iloh Antarini; Nony Puspawati; Rahmat Budi Nugroho (Program Studi Teknologi Laboratorium Medik, 2021)
Some plants such as Moringa, green tea, binahong, and green meniran can be used as alternative antimicrobials because they are proven to contain antibacterial compounds. This study aimed to determine the antibacterial activity of the ethanolic extracts of Moringa leaves, green tea leaves, binahong leaves, and green meniran against Pseudomonas aeruginosa ATCC 27853. The extracts were obtained by maceration method with 70% ethanol solvent and tested for their antibacterial activity using the well diffusion method with a concentration of 60%. The results showed that the ethanolic extracts of Moringa leaves, green tea leaves, binahong leaves, and green meniran had antibacterial activity against Pseudomonas aeruginosa ATCC 27853 with inhibitory powers of 20.6 mm, 17.3 mm, 15.6 mm, and 22.6 mm. Meniran green ethanolic extract has the most active antibacterial activity.